DOSTĘP DO BUDYNKU NA PODSTAWIE SB I 6000 - Skalec, Aneta (Zeszyty Prawnicze, 2016)
Access to a Building on the Grounds of SB I 6000 Summary In densely built-up urban areas access to a property may be a problem, especially if the property is not connected directly to a public network of streets. This was a familiar problem already in ancient times and can be observed in Demotic and Greek papyri from Ptolemaic and Roman Egypt. Despite an abundance of records attesting to the existence of access to property, there are very few documents giving direct evidence for the regulation of access, viz. its establishment or right of use. SB I 6000, dated to the 6th century AD, is one of these rare items, the only extant papyrus exclusively on access to premises. It contains a series of agreements relating to this problem, some on the division of an inherited estate between the members of a family, and others only on access to the property. This document sheds light on an important, but relatively little known legal issue: access to property in non-Roman legal systems.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />